PENGARUH PEMBERIAN SUPLEMEN KALSIUM DALAM PENCEGAHAN PREEKLAMPSI PADA IBU HAMIL TRIMESTER 2 - Iin setiawati; Fika Anjani; Herlin Agustin H (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2018)
During pregnancy, the need for increasedcalcium intake. Adequate calcium intake can reducethe risk of preeclampsia. the survey results ofpreliminary studies in Polindes Asemjaran Banyuates over the pastthree months, Found that three pregnant womendetected preeclampsia from a total of 57 pregnantwomen (5.26%). The purpose of the study to analyzethe effectiveness of calcium in pregnant women topreventing preeclampsia in the working area ofPolindes Asemjaran Banyuates. The research design used was QuasiEksperimen with Non Equivalent Control Groupapproach. The independent variable is CalciumSupplementation and dependence is the Occurrenceof Preeclampsi on Trimester 2 Pregnant Woman. Thesample of this study is trimester 2 pregnant womenwho are at risk of experiencing preeclampsia thatmeet the criteria. The instrument was used theobservation sheet, and analyzed using ParametricTest if qualified and non-parameteric test if notqualified with a 0.05. The result of statistical test in both dose group500 mg and 1000 mg with Paired T-Test wasobtained p value (0,941)> α (0,05) in 500 mg dosegroup and Wilcoxon Signed Rank Test result p value(0,105) > a ( 0.05) at a dose of 1000 mg the meanings H1 and H2 are rejected, there is no differencebefore and after given calcium supplement dose 500mg or 1000 mg to prevent preeclampsi. While in theposttest test with Mann Whitney Test in both groupsobtained results p Value (0.105)> α (0.05), it can beconcluded that supplementation of calcium dose 500mg and 1000 mg not effective to preventpreeclampsia. Calcium supplementation of 1000 mg and 500mg doses has not been proven statistically effectiven preventing preeclampsia. Further research isrecommended to increase the number of samples, sothat the research results will be visible and can begeneralized to all pregnant women.